ANALISIS UNSUR INTRINSIK PUISI DALAM BUKU ANTOLOGI CERPEN DAN PUISI ANAK BALON KEINGINAN PENYUSUN KORRIE LAYUN RAMPAN DAN IMPLIKASI PEMBELAJARAN DI SEKOLAH DASAR - Dina Rainida Ilhami; Dani Gunawan; Risma Nuriyanti (caXra: Jurnal Pendidikan Sekolah Dasar, 2021)
The intrinsic element of this poem can express good poetry being shown the understanding and delusion of poetry, in addition to having an effect to sharpen sensitivity to humanitarian issues. Poetry in the book Anthology Of Short Stories and Poetry of Balon Children The desires of Korrie Layun Rampan is a collection of poems by elementary school students, therefore, students can understand the intrinsic element of poetry in elementary school learning. This research aims to describe the intrinsic elements of poetry and the implications in elementary school. The research method used is descriptive qualitative research. Based on the results of research shows that poetry with the theme of love of the homeland there are 5 poems, humanity there are 12 poems, and patriotism there are 3 poems. While the tone there is a tone advising there are 2 poems, there are 2 poems, there are 2 poems, and pride there are 14 poems. The feelings conveyed are the feeling of anxiety 5 poems, admiration 7 poems, happiness there are 4 poems, and gratitude there are 4 poems. This mandate is grouped by theme, there is a mandate of gratitude to the One God, a mandate to always be sympathetic and empathetic, and always respect and respect that exists in yourself, country, and culture. Related to this in the book Anthology of Short Stories and Poetry Of Children Balon Desire constituents Korrie Layun Rampan 11 poems have implications in learning and 9 poems have no implications in learning. Anthology Book Of Short Stories and Poetry of Children Balloons The desire of Korrie Layun Rampan is expected to add insight and reference of children's reading materials related to literary works.Keywords: Intrinsic Elements of Poetry, Learning Unsur intrinsik puisi ini dapat mengekspresikan puisi yang baik dengan ditunjukkan oleh pemahaman dan penghayatan puisi, selain itu juga berpengaruh untuk mempertajam kepekaan terhadap masalah kemanusiaan. Puisi dalam buku Antologi Cerpen dan Puisi Anak Balon Keinginan penyusun Korrie Layun Rampan ini merupakan kumpulan dari puisi karya siswa sekolah dasar, sehubungan dengan hal itu maka siswa dapat memahami unsur intrinsik puisi dalam pembelajaran di sekolah dasar. Penelitian ini bertujuan untuk mendeskripsikan unsur intrinsik puisi dan implikasi di sekolah dasar. Metode penelitian yang digunakan yaitu penelitian kualitatif deskriptif. Berdasarkan hasil penelitian menunjukkan bahwa puisi dengan tema cinta tanah air terdapat 5 puisi , kemanusiaan terdapat 12 puisi, dan patriotisme terdapat 3 puisi. Sedangkan nadanya terdapat nada menasehati terdapat 2 puisi, ajakan terdapat 2 puisi, kritik terdapat 2 puisi, dan kebanggaan terdapat 14 puisi. Perasaan yang disampaikan yaitu perasaan kegelisahan 5 puisi, kekaguman 7 puisi, kebahagiaan terdapat 4 puisi, dan rasa syukur terdapat 4 puisi. Amanat ini dikelompokkan berdasarkan tema, terdapat amanat rasa syukur kepada Tuhan Yang Maha Esa, amanat untuk selalu bersimpati dan berempati, dan selalu menghormati dan menghargai yang ada dalam diri sendiri, negara, dan budaya. Terkait hal tersebut dalam buku Antologi Cerpen dan Puisi Anak Balon Keinginan penyusun Korrie Layun Rampan 11 puisi berimplikasi dalam pembelajaran dan 9 puisi belum berimplikasi dalam pembelajaran. Buku Antologi Cerpen dan Puisi Anak Balon Keinginan penyusun Korrie Layun Rampan diharapkan dapat menambah wawasan dan referensi bahan bacaan anak terkait karya sastra.Kata Kunci: Unsur Intrinsik Puisi, Pembelajaran